Unusual Presentation of Multisystemic Inflammatory Syndrome - Farah Alnoor Ebrahim; George Moturi; Newnex Mongare; Reena Shah (Case Reports in Medicine)
COVID-19 pneumonia in children presents with very mild symptoms through an entity of multisystem inflammatory syndrome and can result in a life-threatening hyperinflammatory condition, with involvement of at least four organ systems and a marked inflammatory state. We present an 18-year-old high school student who presented with a sore throat, macular rash, abdominal pain, diarrhea, fevers, and joint pains. He presented with acute kidney injury and confusion with multiple tests and was eventually diagnosed with multisystem inflammatory syndrome in children (MIS-C).